Chandra observations of coronal emission from the early-G supergiants Alpha and Beta Aquarii - HARPER, GRAHAM (University of Colorado, 2005)
We report Chandra detections of coronal X-rays from the early-G supergiants ? Aquarii (HD209750: G2 Ib) and ? Aquarii (HD204867: G0 Ib). Previous ROSAT observations of these archetype \hybrid chromosphere" stars were in- conclusive in the case of ? Aqr, owing to a 380 mispointing; and although clearly detecting a source near ? Aqr, a small positional discrepancy called the iden- ti?cation into question. The Chandra High Resolution Camera (HRC-I), with its superior spatial resolution and sensitivity, has obtained a positive detection of ? Aqr, and recovered faint emission at the location of ? Aqr, now well sepa- rated from the stronger source to the SE that dominated the earlier ROSAT im- age. The coronal LX=LC IV luminosity ratios of both supergiants are extremely depressed relative to early-G main sequence stars, continuing the \X-ray de?- ciency" trend originally identi?ed in late-F/early-G luminosity class III giants of the Hertzsprung gap.
PUBLISHED
Keywords: Stars: individual | X-rays: coronae | ultraviolet: spectra